Phytochemical and Antibacterial Investigations of the Extracts and Fractions from the Stem Bark of Hymenaea stigonocarpa Mart. ex Hayne and Effect on Ultrastructure of Staphylococcus aureus Induced by Hydroalcoholic Extract. (14th December 2013) - Dimech, Gustavo Santiago; Soares, Luiz Alberto Lira; Ferreira, Magda Assunção; de Oliveira, Anne Gabrielle Vasconcelos; Carvalho, Maria da Conceição; Ximenes, Eulália Azevedo
Abstract : The aim of this study was to investigate the antimicrobial activity of different extracts and fractions obtained from Hymenaea stigonocarpa stem barks. The cyclohexanic, ethyl acetate, ethanol, aqueous, and hydroalcoholic extracts were obtained by maceration. The hydroalcoholic extract was partitioned, which resulted in the ethyl acetate and aqueous fractions. All extracts and fractions were subjected to phytochemical screening and evaluation of total phenol and tannin contents. An HPLC-DAD and ultrastructural alterations analysis were performed. Terpenes and coumarins were detected in the cyclohexanic extract. Flavonoids and condensed tannins were present in the other extracts and fractions. The extracts with the highest contents of tannins, ethanol (EE), hydroalcoholic (HE), and aqueous fraction (AF) showed also the highest antimicrobial activity. The MIC values ranged from 64 to 526 µg/mL. The chromatographic fingerprints suggest the presence of astilbin and other flavonoids in EE and HE. Presence of the thick cell wall, undulating outer layer, abnormal septa, and leakage of the cytoplasmic contents and absence of cell wall and cell lyses were the main alterations observed on Staphylococcus aureus ATCC 33591 after treatment with the Hymenaea stigonocarpa hydroalcoholic extract. The presence of phenolic compounds like flavonoids and tannins is possibly the reason for the antimicrobial activity.